2013
DOI: 10.13075/mp.5893.2013.0059
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and Its Formulations - Toxicity, Occupational and Environmental Exposure

Abstract: Glyphosate (N-(phosphonomethyl)glycine) is an active ingredient of the most widely used herbicide formulations in protecting agricultural and horticultural crops. Numerous results (mostly published in the years 2010-2013) concerning the action of glyphosate and its formulations in the recent decade were analyzed. Initial reports about alleged biodegradability of glyphosate in the environment turned out to be wrong. It has been shown that glyphosate remains in the soil and can reach people by spreading along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…This disruption may affect the supply of human organism with essential amino acids ( 85 ). Commercial glyphosate formulations are considered to be more toxic than the active substance alone ( 80 , 83 , 86 , 87 ). Glyphosate-based herbicides, such as the well-known “Roundup,” can cause DNA damages and act as endocrine disruptors in human cell lines ( 60 ) and in rat testicular cells ( 88 ), cause damages to cultured human cutaneous cells ( 89 ), and promote cell death in the testicular cells of experimental animals ( 88 , 90 ).…”
Section: Organophosphorus Pesticidesmentioning
confidence: 99%
“…This disruption may affect the supply of human organism with essential amino acids ( 85 ). Commercial glyphosate formulations are considered to be more toxic than the active substance alone ( 80 , 83 , 86 , 87 ). Glyphosate-based herbicides, such as the well-known “Roundup,” can cause DNA damages and act as endocrine disruptors in human cell lines ( 60 ) and in rat testicular cells ( 88 ), cause damages to cultured human cutaneous cells ( 89 ), and promote cell death in the testicular cells of experimental animals ( 88 , 90 ).…”
Section: Organophosphorus Pesticidesmentioning
confidence: 99%
“…; Kwiatkowska et al. ). High water solubility has guaranteed its distribution in aquatic ecosystems, where its toxic impact has been seen in fish (Menendez‐Helman et al.…”
Section: Prevalence In the Environmentmentioning
confidence: 98%
“…It is generally assumed that glyphosate does not persist in the environment due to sedimentation and breakdown by microorganisms (Battaglin et al 2005). However, residues of glyphosate, and its main metabolite AMPA, have been found in both food and water sources, indicating the potential risks for frequent, long-term exposure (Landry et al 2005;Mañas et al 2009;Kwiatkowska et al 2013). High water solubility has guaranteed its distribution in aquatic ecosystems, where its toxic impact has been seen in fish (Menendez-Helman et al 2012;Braz-Mota et al 2015), insects (Pérez et al 2011), and birds (Oliveira et al 2007).…”
Section: Prevalence In the Environmentmentioning
confidence: 99%
“…In the last years it was shown that glyphosate does not give in to fast biodegradation, it stays in soil and it may reach to earth water. It was demonstrated that glyphosate with low concentration is detected in blood serum of people (Kwiatkowska et al 2013). It may induce cancerous changes and affect on hormonal ones.…”
Section: )mentioning
confidence: 99%